The challenges in maintaining green office building at Malaysia / Suzilawani Sulaiman - Sulaiman, Suzilawani (Faculty of Architecture, Planning and Surveying, 2015)
The Green building development has become a trend in recent years because it giving many benefit especially on environmental, social and economic aspect. However, many have argued that the complexities rendered by green buildings during the operational and maintenance phase often overshadow the benefits that can be gained through the development of green buildings. Several factors that lead to complexities in managing and maintaining green buildings. There are many barriers that maintenance team faced in maintaining green office building. This study determines the challenges in maintaining green office buildings in Malaysia. As an effort to shed light into this issue, a questionnaire survey and interview was carried out involving green office building maintenance management teams in Putrajaya Holding Building, Diamond Building, Low Energy Office (LEO) Building and Digi Technology Operation Centre Building. Frequency and criticality index calculations were carried out to rank the factors according to level of agreement from the respondent based on questionnaire and interview session. The result indicated there are three factors of challenges in maintaining green office building which is technical factor, managerial factor and environmental and biological effect. The common problem and challenges factor in maintaining green office building is managerial factor.